2018
DOI: 10.1002/ange.201712027
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Fenton‐like Ion Delivery and Glutathione Depletion by MnO2‐Based Nanoagent to Enhance Chemodynamic Therapy

Abstract: Chemodynamic therapy (CDT) utilizes iron‐initiated Fenton chemistry to destroy tumor cells by converting endogenous H2O2 into the highly toxic hydroxyl radical (.OH). There is a paucity of Fenton‐like metal‐based CDT agents. Intracellular glutathione (GSH) with .OH scavenging ability greatly reduces CDT efficacy. A self‐reinforcing CDT nanoagent based on MnO2 is reported that has both Fenton‐like Mn2+ delivery and GSH depletion properties. In the presence of HCO3−, which is abundant in the physiological medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
204
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(212 citation statements)
references
References 40 publications
4
204
0
Order By: Relevance
“…It was worth noting that Hcy and Cys, the two biological thiols that may severely affect GSH detection, did not interfere with the GSH detection in our system. /HCO 3 − ) buffer solution are all necessary to fade the blue MB solution, which was in accordance with the previous work [58]. Additionally, the results of groups 4 and 5 indicated that the added GSH eliminated the formed ⋅ OH and inhibited the MB degradation.…”
Section: Gsh Detectionsupporting
confidence: 90%
See 2 more Smart Citations
“…It was worth noting that Hcy and Cys, the two biological thiols that may severely affect GSH detection, did not interfere with the GSH detection in our system. /HCO 3 − ) buffer solution are all necessary to fade the blue MB solution, which was in accordance with the previous work [58]. Additionally, the results of groups 4 and 5 indicated that the added GSH eliminated the formed ⋅ OH and inhibited the MB degradation.…”
Section: Gsh Detectionsupporting
confidence: 90%
“…However, at high DOX concentrations (10-20 μg mL −1 ), EMD NSs showed the relatively higher cytotoxicity than free DOX ( Figure 5(h)), so we assumed that some other factors may also play roles in the EMD NS-induced cell death. Although EM NSs caused negligible changes in the cell viabilities, the substantial accumulation of ROS was observed in the EM NS-or EMD NS-treated cells (Figure 5(l) and Figure S13), which could be attributed to the conversion of endogenous H 2 O 2 to highly reactive ⋅ OH (one of the most harmful forms of ROS) induced by the Mn 2+ -mediated Fenton-like reaction [58]. Importantly, based on the in vitro EM NS-assisted O 2 generation results (Figure 4(a)), EM NSs showed great promise in downregulating the P-gp expression by increasing the O 2 level under hypoxia.…”
Section: Different Effects Of Emd Nss On Cancer/normal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several alternative therapies have been proposed and investigated in the treatment of glioblastoma. Phototherapy, utilizing a light‐powered photochemical reaction as in photodynamic therapy (PDT), and localized hyperthermia have attracted considerable attention as alternatives to conventional radiotherapy and chemotherapy . The photoacoustic (PA) shockwave, created by the cavitation (growth and collapse) of nanobubbles and microbubbles around nanoparticles heated by laser pulses, produces a strong and localized mechanical disruption of the tissue it comes into contact with .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that MnO 2 is stable in the bloodstream with low r 1 and r 2 values. However, it can react with TME-enriched acid and H 2 O 2 to generate Mn 2+ , which is a potent MRI T 1 contrast agent (20). The above results indicated that the aPD-1-decorated nanomicelle (MnO 2 @PPC-aPD-1) accumulated much more effectively in the tumor sites of animals with CUR pretreatment (the CT-aPD-1 group) than the antibody isotype-decorated nanomicelle (MnO 2 @ PPC-Iso) in the tumor sites of animals with CUR pretreatment (the CT-Iso group) or without CUR pretreatment (the NCT-Iso group).…”
Section: Drug Delivery In Vivomentioning
confidence: 99%